Donor human milk practice in Indonesia: a media content analysis - Pramono, Andini; Hikmawati, Alvia (Frontiers in Nutrition, 2024)
Introduction Donor human milk (DHM) is recommended as the second-best alternative form of supplementation when a mother is unable to breastfeed directly. However, little is known about the experience of mothers and families in the communities regarding accessing and donating expressed breastmilk in Indonesia. This study aimed to identify the experience related to donor human milk in the society in Indonesia. Method A search was conducted through six main online news portals. The keywords used included “donor human milk,” “expressed breastmilk,” and “wet nursing” in the Indonesian language, Bahasa Indonesia. A total of 107 articles were found, but only 20 articles were included for analysis using a qualitative media content analysis approach. Results In the study, the following five themes were identified: (1) the whys and wherefores of donor human milk, (2) national and religious-based regulations, (3) recommendations from authorized organizations, healthcare professionals, and Islamic scholars, (4) the negative impact from the lack of national regulations, and (5) contradictory feelings among mothers. Conclusion With the lack of detailed information on how to access or donate expressed human milk and the absence of a human milk bank in place, informal human milk sharing is inevitably occurring in the community. This has also raised concerns among authorized organizations, healthcare professionals, and Islamic scholars. Consequently, mothers, both donors and recipients, experienced negative impacts, which included contradictory feelings. Engaging with Islamic scholars and healthcare professionals to develop clear guidelines and regulations to enable mothers' and families' access and/or make contributions to DHM in a safe and accountable way is critical to prevent further problems from occurring in Indonesian society.